2016
DOI: 10.4136/ambi-agua.1694
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological assessment of C57Bl/J mice organs exposed to tannery effluents

Abstract: The effluent produced in tanneries can cause environmental damage and public health problems when disposed of improperly. However, few toxicological studies have evaluated the effects of the intake of tannery wastewater by mammals. The objective of this study is the histological assessment of organs of C57Bl/J mice exposed to the intake of different concentrations of raw tannery effluents, beginning with the hypothesis that these effluents can cause damage to the histological structure of the organs. The anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The possible action of organic and inorganic effluent components on the normal functioning of the central nervous system can explain the diversity of herein observed behavioral effects. According to Souza et al (2016a), variables such as sex, age, effluent type (derived from different bovine skin processing stages), rodent species and lines and effluent concentration, are important factors contributing to different results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible action of organic and inorganic effluent components on the normal functioning of the central nervous system can explain the diversity of herein observed behavioral effects. According to Souza et al (2016a), variables such as sex, age, effluent type (derived from different bovine skin processing stages), rodent species and lines and effluent concentration, are important factors contributing to different results.…”
Section: Resultsmentioning
confidence: 99%
“…Murine experimental models can help in understanding the effects of contact with tannery effluent on the central nervous system, since clinical neurobehavioral research involving tannery workers is almost nonexistent. Some studies simulated tannery effluent exposure in an animal-analysis laboratory environment in order to assess the intake of water contaminated with tannery effluent (Siqueira et al, 2011;Moysés et al, 2014;Souza et al, 2016a;2016b;Guimarães et al, 2016a;2016b;Rabelo et al, 2016;Guimarães et al, 2017). However, these studies are incipient when it comes to the effects of dermal tannery effluent on laboratory animals.…”
Section: Introductionmentioning
confidence: 99%
“…In Souza et al (2016), moderate hydropic degeneration was detected in animals (C57Bl/6J mice) exposed to tannery effluents, mainly in the periportal space. A large number of necrotic hepatocytes were detected, especially in animals exposed to higher tannery effluent concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few authors have evaluated the effect of tannery effluents on mammals, among which are Kumar et al (2008), Siqueira et al (2011), Moysés et al (2014, Silva et al (2015), Lemos et al (2015), Ferreira et al (2015), Souza et al (2016) and Rabelo et al (2016). In the pioneering study by Kumar et al (2008), chronically exposing male Wistar rats to tannery effluent, the authors observed a mass increase of all of the androgen-dependent organs evaluated, such as the prostate and seminal vesicle, and found deformations in the seminiferous tubules with testicular hyperplasia signals.…”
Section: Introductionmentioning
confidence: 99%